A Normative Analysis of the Inheritance Rights of Adopted Children from the Perspective of Indonesian Positive Law - Rahma Nuraulia A. Tabukali; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Eastasouth Institute, 2026)
This study examines the inconsistencies in the regulation of inheritance rights for adopted children within Indonesia’s positive legal system, which is influenced by legal pluralism namely, civil law, Islamic law, and customary law. The primary issue lies in the inconsistency of legal norms, which creates legal uncertainty and the potential for injustice toward adopted children who, sociologically speaking, have become part of the family. This study aims to analyze the normative status of adopted children in inheritance matters and to identify the conflicts of norms that arise. The method used is normative legal research employing legislative, conceptual, and comparative approaches, analyzed qualitatively through legal interpretation and argumentation. The results of the study indicate that adopted children have not been consistently recognized as heirs, with limited solutions such as mandatory wills that do not fully guarantee substantive justice. Furthermore, differences in judicial interpretation reinforce legal uncertainty in practice. This study underscores the importance of harmonizing and reforming inheritance law to create legal certainty and justice that is more responsive to social realities.